JAK2 mutation in unusual thrombotic patients without myeloproliferative neoplasm: the clinical significance - Jamhuri, Nur Syazwani; Ibrahim, Ismail; Ruslan, Mohamad Azhari (Elsevier, 2024)
Background: JAK2 V617F mutation is one of the driver mutations for myeloproliferative neoplasm (MPN) and vascular thrombosis. Its allele burden impacts on clinical phenotype of the neoplasm and contributes to higher risk of vascular thrombosis, especially venous thrombosis. However, in general population with JAK2 V617F mutation without overt MPN, the clinical significance of this mutation is still an enigma. Aims: To review the clinical significance of positive JAK2 V617F mutation on the progression to MPN, significant of allele burden and management of anticoagulant in general population without MPN. Methods: This case series involved two cases of vascular thrombosis in patient with no MPN, but with presence of JAK2 V617F mutation. These to illustrate the clinical scenarios for the discussion on the impact of JAK2 V617F mutation on the progression to MPN, risk of vascular thrombosis and management of anticoagulant. Results: Few studies managed to report JAK2 V617F mutation positive general population does progress from absent to overt MPN, and this is linearly corresponded to allele burden. Presence of this mutation is also associated with higher cumulative risk of thrombosis (venous and arterial) even without MPN. With the presence of thrombosis, no guideline is yet available to help navigating management. Perhaps, references can be made on available management guide for MPN patients with thrombosis. Conclusion(s): JAK2 V617F mutation does have a role to play in progression to MPN, shaping the clinical phenotype, and risk of vascular thrombosis even in general cohort. JAK2 V617F mutation allele burden also shows a significant association to the above, though the standardized cut off value is unknown. With more knowledge, it will impact the clinical practice on general cohort with JAK2 V617F mutation; closer monitoring for development of MPN, vascular complication and management of anticoagulant.